Obtenção de extratos bioativos de Calophyllum brasiliense Cambess utilizando fluido pressurizado - Gonçalves, Renata Menoci (2011)
The Calophyllum brasiliense Cambess (Clusiaceae), known popularly as guanandi, is used to treat bronchitis, gastric and hepatic disorders, pain, inflammation, diabetes, hypertension, diarrhea, and herpes. Plants of this kind have been a rich source of bioactive substances including coumarins, xanthones, steroids, triterpenes and biflavonoids. Among the different methods for extraction of bioactive compounds of plant materials, it can be highlighted the supercritical extraction, a process of high-pressure separation, free from toxic waste, which doesn't cause thermal degradation to extracts and preserves the quality of thermosensitive products. The objective of this study was the extraction of bioactive compounds from the leaves of Calophyllum brasiliense via supercritical extraction (SCE) and conventional extraction in order to determine the performance of the process, the composition and biological activities of the extracts. The operating conditions for the extraction of pressurized CO2 were 40 and 60 ° C and pressures ranging from 109.2 to 250 bar, and for the conventional extraction solvents dichloromethane and hexane were used. The best performance was obtained for the extraction with dichloromethane, though this was the extract that presented the lowest content of (-) mammea A/BB, while the ESC showed the best performance in the condition of 60 ° C and 244.1 bar. The Mathematical modeling of second-order fit well the experimental data. The antioxidant activity of extracts, using the method of reduction of DPPH_ in the extracts studied did not present a good result. The content of total phenols was high, which was already expected, since the plants of this kind are composed of bioactive substances including coumarins, xanthones and biflavonoids. It was also observed that the concentration of cumarima (-) mammea A/BB, chemical marker, was higher in extracts obtained with pressurized fluid. The quantification of this compound is important due to the fact that the substances of this class show potent pharmacological activities and relevant and are of low toxicity to mammals. The analysis showed that none of the antibacterial extracts presented activity against the Gram-negative microorganisms, as against the Gram-positive the extracts obtained via the SCE were strongly active with MIC between 15.62 and 31.2 μg/mL for Staphylococcus aureus and between 3.91 and 7.81 μg/mL for S. aureus multiresistant and presented a good selectivity index against the macrophage J774G8. For the antifungal activity the extract obtained with dichloromethane presented a better result for all the microorganisms tested. The results obtained showed that the SCE is an efficient method to obtain bioactive compounds of C. brasiliense, preserving the properties associated with the antimicrobial activity.